The Effect of Soybean Milk on Increasing Breast Milk Production in Postpartum Mothers in Salambue Village, Southeast Padangsidimpuan District - Dewi Aminasty Siregar; Maryam Latifah Harahap; Eva Yusnita Nasution (PT Inovasi Pratama Internasional, 2022)
Breast milk consists of several elements such as water, enzymes, nutrients, hormones, antibodies which are difficult for humans to imitate. One of the factors that cause a lack of breastfeeding is less milk production. Many factors cause a lack of smooth breastfeeding, namely problems with the mother, including inverted nipples, mastitis or breast abscess, swollen breasts, and sore nipples. In infants, it is generally an error in lactation management, which causes a decrease in milk production. The purpose of this study was to determine how the effect of soy bean milk on increasing breast milk production in postpartum mothers in Salambue Village, Southeast Padangsidimpuan District. The type of research used is experimental research with a prettest posttest only control group design. Using purposive sampling with the number of respondents as many as 8 people, namely the experimental group respondents as many as 4 people and the control group as many as 4 people. Based on the results of the study, it showed that there was an effect of giving soy bean milk to the increase in breast milk production in postpartum mothers in Salambue Village, Southeast Padangsidimpuan District with p-value <0.05 it mean Ho is rejected and Ha is accepted.